Comparison of physical, microstructural and antioxidative properties of pumpkin cubes cooked by conventional, vacuum cooking and sous vide methods. (30th October 2020) - Rinaldi, Massimiliano; Santi, Saverio; Paciulli, Maria; Ganino, Tommaso; Pellegrini, Nicoletta; Visconti, Attilio; Vitaglione, Paola; Barbanti, Davide; Chiavaro, Emma
Abstract: BACKGROUND: Current dietary guidelines recommend five or more fruit, vegetable, and legume servings per day. Often, these products are eaten cooked, resulting in organoleptic and nutritional changes. Vacuum cooking is gaining attention as an alternative cooking technique, due to its ability to preserve or even enhance sensory and healthy properties of food. Its household application is, however, poorly explored. In this work, the effect of vacuum cooking, performed with a new patented system, was studied for the first time on pumpkin cubes and compared to sous vide and traditional steam cooking, through a multidisciplinary approach. RESULTS: All the cooking treatments damaged pumpkin microstructure, leading to cell separation and plasmolysis; vacuum cooking was the most aggressive method, as confirmed by texture softening. Vacuum cooking was also the method with less impact on pumpkin color, in relation to the largest extraction of some classes of carotenoids from the broken cells. Significant polyphenol extraction, especially of gallic acid and naringenin, was instead observed for sous vide and steamed pumpkins. The total antioxidant activity, ascribable to the effect of both carotenoids and polyphenols, resulted enhanced after cooking compared to raw one mainly for cook vide samples, followed by steamed and sous vide ones. CONCLUSIONS: Vacuum cooking, followed by sous vide, has often shown better performance than traditional steam cooking for pumpkin cubes. The implementation of sous vide and vacuum cooking at domestic level or in professional kitchens, and in the food industry, would allow the consumption of vegetables with improved nutritional and sensorial characteristics. © 2020 Society of Chemical Industry